Epidemiological features of healthcare associated infection of newborns in the Russian Federation during 2007–2017 - M. V. Ivanova; A. Ya. Mindlina (Журнал инфектологии)
Objective: to offer additional criteria for assessing registration quality of congenital infections and neonates’ pyoseptic infections. Material and methods: a retrospective epidemiological analysis of congenital infections incidence, pyoseptic infections of puerperas and neonates during 2007–2017 was conducted in this study. All subjects of the Russian Federation were divided into some groups according to registered incidence rate and ratio among congenital, pyoseptic infections of puerperas and neonates with using the method of ranging. Comparative correlation analysis was conducted between puerperas’ pyoseptic infections and neonates’ congenital infections in accordance with registered rate. The sample of the date was taken from Statistical Reporting Form No 2 «Report on infectious and parasitic diseases» for the Russian Federation during 2007–2017, Unified interdepartmental information and statistical system. Results: in most regions of the Russian Federation the registration of healthcare associated infections puerperas and neonates is at a low. More than a half of subjects have low incidence rates (less than 1,0) for one or more of the considered infections. Until now, there are several subjects that do not register healthcare associated infections at all. The absence of correlation relation between the morbidity of the puerperas’ pyoseptic infections and neonates’ congenital infections on the whole in the country confirms this fact. At the same time, the correlation analysis of separate regions with the registration close to the real figures has shown a strong positive relationship between puerperas’ pyoseptic infections and congenital infections. Conclusion: thus, it can be concluded that the presence of relation between rates of incidence of puerperas’ healthcare associated infections and neonates’ congenital infections can be used as one of the epidemiological criteria for assessing the completeness of the registration of healthcare associated infections.